Ranking of Corporate Social Responsibility of Firms - Darbinyan, Armenak; Budaghyan, Davit (Bulletin of Yerevan University G: Economics, 2016)
This article introduces an approach for ranking corporate social responsibility (CSR) of organizations, the theoretic base of which is Carroll’s CSR Pyramid. Ranking is based on the levels of economic, legal, ethical and discretionary responsibilities of the firm. This is performed using information entropy and VIKOR multifactorial decision making method. The article also includes a hypothetical example of application of the proposed approach.
Keywords: corporate social responsibility, stakeholder theory, CSR pyramid, ranking, method VIKOR, information entropy